Risk Assessment of Occupational Exposure of Refinery Unit Site Staffs to Benzene, Toluene, Ethyl Benzene, Xylene Compounds (BTEX) in an Oil Company - maghsoud ghasemi poor; nastaran mollazadeh (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: In most process units of refinery industries, staffs are exposed to various chemical agents. The purpose of this study was to identify the highest level of occupational exposure to Benzene, Toluene, Ethyl Benzene, Xylene compounds (BTEX)and to assess the risk caused by them in staffs of an Oil Company. Methods: Initially, the staffs' tasks, work processes, and harmful factors in the working environment were determined based on the occupational groups. Then, 10 site staffs, who were in the same shift work were selected. According to NIOSH method number 1501, air sampling and BTEX analysis were performed. To analyze the results, IHSTAT software of American industrial hygiene association was applied. Finally, the risk assessment was done in accordance with the method number 84101042 of Oil Ministry. Results: The statistical analysis of the measures indicated that exposure to toluene, ethylene benzene, and xylene was at the permitted level, but high exposure to benzene was not determined. The risk assessment showed that Benzene had a medium risk rating. Moreover, Toluene, Ethyl Benzene, and xylene had low risk rating Conclusion: According to the severe consequences of benzene exposure, corrective and preventive measures should be taken to remove or decrease the exposure rate.